Freeze-Dried Muscadine grape: a New Product for Health-Conscious Consumers and the Food Industry - Ali Sarkhosh; Fariborz Habibi; Steven A. Sargent (EDIS)
Muscadine grape (Muscadinia rotundifolia [Michx.]) is a fruit crop native to America; it adapts well to a wide range of biotic and abiotic stresses and have thus been grown and vinified throughout the southeastern US for centuries. Currently, southeastern farmers grow approximately 5,000 acres of almost 100 improved muscadine-grape varieties for commercial use. Recent research demonstrated the fruit’s significant contribution of beneficial phytochemicals to the typical American diet; and thereafter, the demand for muscadine grapes considerably increased. Its thick peels and seeds, though, have prevented wider public consumption. This publication aims to introduce growers, Extension agents/specialists, and the general public to the potential for a new, value-added product that makes muscadine grapes much easier to eat and may diversify the food processing industry.